The Use of an Erector Spinae Plane Block for Perioperative Pain Management for a Neonatal Thoracotomy in a Resource-limited Setting: A Case Report - Mellissa Delcont; Eunice Kageha; Amos Zacharia; Richard Hubbard (The Annals of African Surgery)
Adequate pain control for neonates undergoing thoracotomies can be challenging to accomplish without inducing respiratory depression from opioid administration. Premature neonates with cardiac and respiratory comorbidities are at increased risk of respiratory complications, and this risk further increases in resource-limited environments with shortages of skilled healthcare providers and equipment. Erector spinae plane (ESP) blocks have been shown to reduce opioid consumption post-operatively in neonates undergoing thoracic surgery in middle and high sociodemographic countries, but there are scant reports in the literature translating such advances to low-resource settings. In this case report, we describe the use of an ESP block in a limited critical care capacity setting to facilitate the early extubation of a 5-day-old infant undergoing thoracotomy for tracheoesophageal fistula repair. This case highlights that low-risk, low-cost, and easily teachable regional anesthetic techniques such as ESP blocks offer an excellent option in a multitude of surgical settings.